Prevalence and Incidence of Dry Eye Disease in Asia: A Systematic Review and Meta-Analysis - Cai, Youran; Wei, Jintao; Zhou, Jiaxin; Zou, Wenjin (Ophthalmic research, 2022)
Abstract Background: Dry eye disease (DED) is the most common ocular surface disease, which severely affects the quality of life. An overall estimate of the prevalence, incidence, and risk factors of DED in Asia would help in planning and implementing appropriate public health strategies. Objectives: The present study aimed to study the epidemiology of DED in Asia. Methods: A comprehensive and systematic search was performed using several databases, including PubMed, Cochrane Library, and Web of Science, in January 2021. A random-effects meta-analysis was performed on logit-transformed prevalence and incidence rates to calculate pooled prevalence and incidence estimates. Meta-regression and subgroup analyses were performed to explain the heterogeneity. Results: Among the 6,742 articles identified, 23 were included in the analysis, with a total sample size of 1,488,935 subjects. Twenty studies reported the prevalence of DED in Asia, two studies reported the incidence, and one study reported both prevalence and incidence. The estimated pooled prevalence of DED in any population in Asia was 20.1% (95% confidence interval [Ozdemir et al., Acta Ophthalmol. 2019;97(1):e91–6]: 13.9–28.3%), and the incidence 16.7% (95% CI: 0–34.9%). The prevalence rate of DED in males and females was 16.4% (95% CI: 10.0–25.8%) and 21.7% (95% CI: 14.7–30.8%; p < 0.001), respectively. In general, the prevalence increased with age. The risk factors considered for specific populations were not significant, and the prevalence in the general population, excluding the populations considered at risk, was similar at 20.9% (95% CI: 12.8–32.1%). Conclusions: DED is common in Asian populations and causes a significant disease burden. Its prevalence is higher in females than that in males, and it tends to increase in severity with age. Further research on additional risk factors is needed to adequately explain the epidemiology of DED in Asia.